2011
DOI: 10.1186/1471-2148-11-147
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and androgenesis in the invasive Corbicula clams (Bivalvia, Corbiculidae) in Western Europe

Abstract: BackgroundThe genus Corbicula is one of the most invasive groups of molluscs. It includes both sexual and androgenetic lineages. The present study re-assessed the different morphotypes and haplotypes of West European Corbicula in order to clarify their taxonomic identification and phylogenetic relationships with American and Asian Corbicula clams. We studied several populations from West European river basins (Meuse, Seine, Rhine and Rhône) through an "integrative taxonomy" approach. We combined morphology, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
110
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(136 citation statements)
references
References 56 publications
9
110
0
1
Order By: Relevance
“…In general, individuals of the same morphotype across androgenetic Corbicula share the same mitochondrial and nuclear haplotypes (Park and Kim, 2003;Lee et al, 2005;Hedtke et al, 2008;Pigneur et al, 2011a, b). However, mitochondrial lineages discordant with morphology have been reported in several populations of Corbicula in Asia, America and Europe (Park et al, 2002;Pfenninger et al, 2002;Lee et al, 2005;Hedtke et al, 2008;Pigneur et al, 2011b;see Figure 3). For example, invasive forms in the Americas and Europe are fixed across most of their range for unique mitochondrial haplotypes, but, in some populations, individuals of one morphological form harbor the mitochondrial COI sequence of the other form (for example, between forms A and B, B and C or R and S; Pfenninger et al, 2002;Lee et al, 2005;Hedtke et al, 2008;Pigneur et al, 2011b).…”
Section: Fertilization and Maternal Meiosis In Androgeneticmentioning
confidence: 99%
See 4 more Smart Citations
“…In general, individuals of the same morphotype across androgenetic Corbicula share the same mitochondrial and nuclear haplotypes (Park and Kim, 2003;Lee et al, 2005;Hedtke et al, 2008;Pigneur et al, 2011a, b). However, mitochondrial lineages discordant with morphology have been reported in several populations of Corbicula in Asia, America and Europe (Park et al, 2002;Pfenninger et al, 2002;Lee et al, 2005;Hedtke et al, 2008;Pigneur et al, 2011b;see Figure 3). For example, invasive forms in the Americas and Europe are fixed across most of their range for unique mitochondrial haplotypes, but, in some populations, individuals of one morphological form harbor the mitochondrial COI sequence of the other form (for example, between forms A and B, B and C or R and S; Pfenninger et al, 2002;Lee et al, 2005;Hedtke et al, 2008;Pigneur et al, 2011b).…”
Section: Fertilization and Maternal Meiosis In Androgeneticmentioning
confidence: 99%
“…Ishibashi et al (2003) concluded that, in Corbicula, unreduced biflagellate sperm could be considered indicative of androgenesis. The presence of biflagellate sperm in the invasive lineages in the Americas (Lee et al, 2005; Table 2 and Figure 3) and Europe (Pigneur et al, 2011b; Table 2 and Figure 3) suggests that androgenesis is the most likely reproductive mode in invasive Corbicula.…”
Section: Androgenetic Spermmentioning
confidence: 99%
See 3 more Smart Citations